Development of Digital Comic Media Based on Education for Sustainable Development (ESD) to Improve Cultural and Citizenship Literacy of Elementary Students - Ramadhany, Eka Putri; Darmayanti, Mela; Kurniasih, Kurniasih; Syaripudin, Tatang (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to develop digital comics media to increase studentsâ€™ cultural and citizenship literacy based on Education for Sustainable Development (ESD). This research used the design and development research method with the ADDIE model, which includes five research stages: design, development, implementation, and evaluation. Participants in this research were material experts, media experts, learning experts, and fourth-grade elementary school students. Data collection techniques were carried out using expert validation and tests. Data was analyzed qualitatively and quantitatively. The expert validation results from the three experts are categorized as excellent. The N-Gain result of students’ cultural literacy and citizenship is 0.75 in the high category. The digital comic media developed was feasible and could be used by educators and students as a learning medium for cultural diversity material to increase cultural literacy and citizenship for Elementary School students.